Elite and Empowerment of Local Communities: The Dilemma Between Participation and Mobilization in The Era of Democracy - Hanantyo Sri Nugroho; Desiana Rizka Fimmastuti (Journal of Governance, 2020)
This article discusses the role of local elites in stimulating community participation in various development programs. As is well known, the Serut Hamlet area in Bantul Regency is fostered by private institutions, while the Blue Lagoon Tourism Village is a village that grows for the benefit of the community's economy. This is where the challenge of empowerment will emerge, namely the many activities that only end in a momentary 'project'. By using a qualitative approach in the form of case studies, our study shows that the contribution of the elite in the empowerment process can be said to be quite large. As it is known, the formal elite, in this case the head of the tourism village management and the hamlet head, are the owners of sufficient power to open and close access to empowerment activities. This is reinforced by the ability of the elite to "care for" the sustainability of activities through various means, namely optimization and mobilization. This elite ability is what makes it a determining factor in the success of community empowerment projects.